The Scope for Using the Volatile Profiles of Pinus caribaea var. bahamensis as Indicators of Susceptibility to Pine Tortoise Scale and as Predictors of Environmental Stresses. Issue 4 (April 2015) - Green, Paul W. C.; Hamilton, Martin A.; Sanchez, Michele D.; Corcoran, Marcella R.; Manco, Bryan N.; Malumphy, Chris P.
Abstract Climate change, unseasonal fire and urbanization are contributing to the decline of Pinus caribaea var. bahamensis populations in the Turks and Caicos Islands (TCI). Infestation of pines with the invasive pine tortoise scale (PTS, Toumeyella parvicornis) is accelerating this decline. Pine trees in the Bahamas are larger and healthier and are not infested with PTS although they are subject to some of the same environmental pressures as the trees in TCI. Volatile compounds were collected from wild and nursery‐reared P. caribaea var. bahamensis from TCI and the Bahamas and characterized using GC/MS analysis, to look for differences between the compounds detected in insect‐infested pines of TCI and the healthy pines of the Bahamas. Ten compounds contributing at least 1% of the total detected peak areas in any one of the samples were selected for further study. Eight of these compounds were identified using authentic standards and mass spectral libraries. The main constituents in the samples were α‐ and β‐pinene as well as β‐phellandrene, and, together with β‐myrcene, their contents varied the most between samples collected at different locations. Principal‐component analysis showed that the two structural isomers of pinene, together with β‐myrcene and β‐phellandrene, contributed 98.4% of the variance between samples. There was a positive relationship between the concentrations of the two structural isomers of pinene and between levels of β‐myrcene and β‐phellandrene. The results are discussed in relation to the biology and adaptations of invasive scale insects, the importance of monoterpenes in pine as a defense against insect predation, whether these compounds can be used as indicators of tree health, and future directions for research into conserving the Caicos pine.